2014
DOI: 10.1002/ente.201400012
|View full text |Cite
|
Sign up to set email alerts
|

Demulsification of Water‐in‐Oil Emulsions for the Petroleum Industry by using Alternating Copolymers

Abstract: In this study, a class of hydrophilic‐alternating‐lipophilic copolymers (HaLCs) has been designed, and the polymers were prepared and applied in the demulsification of stable water‐in‐oil (W/O) emulsions. The results showed that the efficiency of HaLCs can reach 100 % in less than 10 min even at room temperature. The optimum dosages for l‐, s‐, and t‐ (linear, square and tetrahedron‐shaped) HaLC were 125, 313, and 156 ppm, respectively. This finding is helpful in understanding the demulsification process and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…317 Using their synthesized alternating hydrophilic-lipophilic copolymers (HaLCs), Yan et al reported a complete demulsification at room temperature in less than 10 min. 456 Aburto et al observed a high demulsification efficiency using a synthetic ionic surface-active choline carboxylate together with microwave irradiation. 457 Rhamnolipid was also found to be able to destabilize the oil-water emulsions.…”
Section: Demulsification Of Heavy Oil Emulsionsmentioning
confidence: 99%
“…317 Using their synthesized alternating hydrophilic-lipophilic copolymers (HaLCs), Yan et al reported a complete demulsification at room temperature in less than 10 min. 456 Aburto et al observed a high demulsification efficiency using a synthetic ionic surface-active choline carboxylate together with microwave irradiation. 457 Rhamnolipid was also found to be able to destabilize the oil-water emulsions.…”
Section: Demulsification Of Heavy Oil Emulsionsmentioning
confidence: 99%
“…The emulsions, including water in oil and oil in water, can be separated into two phases by demulsifiers. The common demulsifiers are generally organic molecules, such as ethylene‐oxide–propylene oxide, amphiphilic block copolymers, hydrophilic‐alternating‐lipophilic copolymers, polyoxyalkylates, diethanolamines, and so on. Most of them are too complicated to synthesize and remain in the oil or water phases after demulsification.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Alvarado investigated how particle suspensions contribute to emulsion stability by characterizing the kaolinite F I G U R E 2 Schematic diagram of the formation of the interfacial films on the O/W interface of asphaltenes and resins [95][96][97][98] and silica particle dispersions as a function of brine salinity in the reference aqueous phase. 50 Scanning electron microscopy (SEM) and X-ray diffraction (XRD) were used to examine the morphology and composition of the clay.…”
Section: Solid Particlesmentioning
confidence: 99%
“…Schematic diagram of the formation of the interfacial films on the O/W interface of asphaltenes and resins 95–98 …”
Section: Formation and Stability Mechanismmentioning
confidence: 99%